Vidal de la Blache historiador - Larissa Alves de Lira (Confins)
This paper aims to situate the geographer Paul Vidal de la Blache (1845-1918) in a slow process of institutionalization of geography in the late nineteenth and early twentieth centuries and in his own transition from historian to geographer. His works on the Mediterranean are crucial for my object, as they go through his entire career, including as a historian. In my attempt to establish the relationship between Vidal and other intellectuals inside and outside the field of geography, I make mine the methodological assumptions of a social history of ideas. I also rely on a history of permanence and continuity for this historical reconstruction, as a methodological approach, which led to the following consideration: in order to avoid anachronisms, it should be noted that Vidal de la Blache has not ceased to be a historian when he became a geographer. His training in history at the École Normale Supérieure and École francaise d’Athènes, and his subsequent relationships with historians (even after been recognized as a geographer), marked his background and career. From this confluence of history and geography emerged an original conception of geographical time. This is the specific notion that I intend to depict and define as an important methodological tool to the study of human geography and, notably, to the field geographer